Adhering to a Mediterranean diet in a Mediterranean country: an excess cost for families? - Alves, R (2021)
Abstract Background: Adherence to the Mediterranean diet has been decreasing in southern Europe, which could be linked to several cultural or educational factors. Our aim is to evaluate the extent to which economic aspects may also play a role, exploring the relationship between food prices in Portugal and adherence to the Mediterranean diet. Methods: We evaluated data from the Portuguese National Food, Nutrition, and Physical Activity Survey (IAN-AF 2015-2016) (n=3,591). Diet expenditures were estimated by attributing a retail price to each food group and the diet was transposed into the Mediterranean Diet Score used in the literature. Prices were gathered from five supermarket chains (65% of the Portuguese market share). Linear regression models were used to assess the association between different adherence levels to the MD levels and dietary costs. Results: Greater adherence to the MD was associated with a 21.2% (p< 0.05) rise in total dietary cost, which accounts for more 0.59€ in mean daily costs when compared with low adherence. High adherence individuals (vs. low adherence) had higher absolute mean daily costs with fish (0.62€/+285.8%; p< 0.05), fruits (0.26€/+115.8%; p< 0.05), and vegetables (0.10€/+100.9%; p< 0.05). The analysis stratified by education and income level showed significantly higher mean daily diet cost only amongst higher income groups. Conclusions: Our findings suggest that greater adherence to the MD was positively and significantly associated with higher total dietary cost. Policies to improve populations diet should take into consideration the cost of healthy foods, especially for large low- and middle-income families.